The tweeting meeting : social media & social networks for meetings & events - Vanneste, Maarten; CMM (S.l. : Meeting Support Institute, 2012)
Introduction: Social media and social networks (SM/SN) are all around us. In just a few years they have taken a place that seems to gain more influence, faster than anything ever before. Also in meetings, conferences, events and exhibitions... Things evolve at high speed and who knows what will be next. What influence does it all have on you? Can you just ignore it and wait until it's over? Or should you start looking for a fulltime SM/SN manager? The truth probably lies somewhere in between these two extremes. I'm sure that after reading this book you will have a better idea of where social media can lead you and how it may help your projects. And despite the title, we are nog only talking about Twitter. Besides the history of social media, - yes, HIS TO RY - we also address groups, communication, marketing, generations, risk, regulating, research and some cases.
Keywords: Sociale media